Inequity in International Climate Change Negotiations - Nanda, Serge Silatsa; Samba, Omar; Sahide, Ahmad (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2021)
The adoption of international climate agreements requires thorough negotiation between parties. This study aims to analyse the inequities between developed and developing countries in climate negotiations. This was done through a scrutiny of the main stages of these negotiations from the Rio Conference to the advent of the Paris Agreement. Our analysis has shown pervasive inequities along the climate negotiations over time. The UNFCCC made a qualitative separation between developed and developing countries in the principle of common but differentiated responsibility. Furthermore, the Kyoto Protocol emphasized this with the commitment of developed countries to reducing their greenhouse gas emissions by at least 5%. The Kyoto Protocol by introducing flexibility mechanisms such as the Clean Development Mechanism (CDM) contributed to increase inequalities. The Paris Agreement has increased inequity by requesting each country to submit nationally determined contributions (NDCs) even though the global emission of developing countries remains very low. The negotiation style of developing countries is mostly limited to compromise and accommodation to the desires of the powerful states, as is the case in most international cooperation. The reality of the climate change negotiations mirrors the inequalities between developed and developing nations.